Краткий справочник школьника: 5-11-й классы / [авторы-составители: П. И. Алтынов и др.] - Алтынов П. И. (Дрофа, 2005)
Экземпляры: ф.16 (2005) / Инвентарный номер: 49070 / Цена: / Сис.шифр: 92 / Авт.знак: К 78 / ББК: 92я721